Strategi Lobi Dan Negosiasi Dalam Mendapatkan Sponsorship Pada Event IKOM Entrepreneurship Fest 2020 - Hakim, Lukman; Nurikhsan, Farhan; Jamil, Hidayat Purwanto; Safitri, Dini (Jurnal InterAct, 2021)
Ikom Entrepreneurship Fest (IEF) 2020 is a webinar event that aims to educate the public, MSME owners, or prospective business people to be able to take advantage of social media to support their business. This event uses a source of funding in the form of sponsorship. To find sponsors, both lobbying and negotiation strategies are needed so that cooperation can run well. The purpose of this research is to find out how the lobbying and negotiation strategies are used by the Public Relations of the IEF 2020 event in obtaining sponsorship for the event. This study used a descriptive qualitative approach and interviews as data collection techniques. The type of data obtained by researchers in this study is primary data. The results of this study state that the lobbying strategy used by the Public Relations of the IEF 2020 event is a direct lobbying strategy with a transactional and networking approach. The negotiation strategy used in this study is the Win-Win negotiation strategy.